Three models to illustrate plant-people relationships in the medicinal plant hotspots of North East India - Jha, Kaushalendra; Smith-Hall, Carsten (Ethnobotany Research and Applications, 2023)
Background: Many indigenous communities inhabit the forests on which they rely. In India, there are many tribe-level plant use records for health treatments but no systematic assessment of the species-level frequency of use or purposes of use across indigenous groups. This paper makes such assessments for North East India. Methods: We did a systematic review of published literature resulting in the identification of a final set of 255 publications for analysis and synthesis. Results: Medicinal plants used by the North East Indian communities in the Himalayan and Indo-Burma hotspots are often used to cure more than one ailment, with phytochemical analysis and clinical tests documenting the efficacy of many species. High-frequency used plant species across indigenous groups were Ageratum conyzoides, Centella asiatica, Clerodendron colebrookianum, Houttuynia cordata, Oroxylum indicum, Spilanthes paniculata, Paederia foetida, Psidium guajava, and Zingiber officinale. We also identified 51 lesser-used species common to more than one indigenous group. Delving into the relationships between plants, tribes, ailments, and locality allowed the identification of three models of people-plant relationships: Plant-Ailment-Tribe; Ailment-Plant-Tribe; and Plant-Locality-Tribe. Conclusions: A large number of indigenous groups using a large number of medicinal plants are found in North East India: uses across groups can be described in three models of people-plant relationships relevant to studying and understanding ethnobotanical realities in other locations. Keywords: Ethnomedicinal plants, frequency use classification, intercultural use, multi-therapeutic attributes